2020
DOI: 10.1175/jcli-d-19-0789.1
|View full text |Cite
|
Sign up to set email alerts
|

Is the North Pacific Victoria Mode a Predictor of Winter Rainfall over South China?

Abstract: This study investigates the connection between the North Pacific Victoria mode (VM) during the boreal spring (February–March–April; FMA) and the following boreal winter (January–February–March; JFM) rainfall over South China (SC). The VM is defined as the second empirical orthogonal function mode (EOF2) of sea surface temperature (SST) anomalies (SSTAs) in the North Pacific poleward of 20°N. It is found that the boreal spring VM has a significant positive correlation with the following winter rainfall over SC.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Sea surface temperature (SST) variability in the North Pacific exerts a substantial influence on the weather and climate patterns over the ocean and adjoining continents, notably affecting North America and East Asia (Beattie & Elsberry, 2012; Ding et al., 2015, 2018; Latif & Barnett, 1994; Tao et al., 2019; Zou et al., 2020). This variability, which constitutes a broader aspect known as the Pacific decadal oscillation, has significant implications for global climate variability (Newman et al., 2016; Vijverberg & Coumou, 2022; Wang et al., 2014; Wei et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Sea surface temperature (SST) variability in the North Pacific exerts a substantial influence on the weather and climate patterns over the ocean and adjoining continents, notably affecting North America and East Asia (Beattie & Elsberry, 2012; Ding et al., 2015, 2018; Latif & Barnett, 1994; Tao et al., 2019; Zou et al., 2020). This variability, which constitutes a broader aspect known as the Pacific decadal oscillation, has significant implications for global climate variability (Newman et al., 2016; Vijverberg & Coumou, 2022; Wang et al., 2014; Wei et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Such a northeast-southwest-oriented SSTA dipole pattern shows significant interannual and interdecadal variability (Ding et al, 2015a). The temporal variability of the VM index has a significant influence on the surrounding Pacific climate, including the Pacific Intertropical Convergence Zone (ITCZ) precipitation (Ding et al, 2015a), the anticyclone over the western North Pacific, and the winter rainfall over South China (Zou et al, 2020) and the western North Pacific tropical cyclone frequency (Pu et al, 2018). It can also be the linkage between North Pacific Gyre Oscillation and ENSO (Ding et al, 2015b) and contribute to the development and propagation of the Madden-Julian Oscillation (Wen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The most recent study to date has demonstrated that the boreal spring North Pacific Victoria mode (VM) is significantly correlated with the following winter precipitation over the SC, and can be regarded as an effective predictor of wintertime precipitation over the SC about 1 year in advance (Zou et al 2020). A positive VM is closely linked to the development of El Niño through surface air-sea coupling and evolution of subsurface ocean temperature anomalies (Ding et al 2015(Ding et al , 2017(Ding et al , 2018(Ding et al , 2019Pu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The most significant correlation between the VM index and Niño 3.4 index occurs when the VM leads El Niño by 11 months. A strong positive VM in spring notably enhances the wintertime precipitation in SC by triggering an El Niño event in the following winter (Zou et al 2020).…”
Section: Introductionmentioning
confidence: 99%